Development of Metal Foam Characteristics Based on Simulation Method - Teo Wee Xuan; Mohamad, Zaleha (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Gas-filled fluid-filled pores make up metal foam. Open-cell and closed-cell metal foam exist. Porosity is the ratio of metal foam pores to volume. Metal foam’s thermal, sound, impact energy, acoustic, and weight characteristics depend on its flow rate and porosity. Thus, metal foam arrangement and substance must be studied. ANSYS Fluent simulation is used to study how foam layout and material affect flow rate and heat transfer. Project development includes modeling, meshing, solution, and analysis. Three arrangement which are uniform, closely pack and mixing are used in analysis the flowrate of the metal foam. Three material for metal foam which are Alumina, Zirconia and Steel are matching with the arrangement to perform rate of heat transfer analysis. The velocity of the inlet is setting as 0.001 m/s while the temperature for the case and fluid are setting as 50 and 30 degree Celsius respectively. Based on the result and analysis, that the design of closely pack arrangement have the highest viscosity which is 3.9897227 〖×10〗^(-4) kg/s, then is uniform arrangement and last is mixing arrangement. While for the rate of heat transfer, the highest value is closely pack alumina which is -6.9879 J/s and the lowest is uniform zirconia which is -2.1718 J/s. As the conclusion, the closely pack alumina is the most desire selection which have the highest viscosity and rate of heat transfer which can apply in decrease its flowrate and fasten the heat dissipation